2018
DOI: 10.3389/fphy.2018.00061
|View full text |Cite
|
Sign up to set email alerts
|

Modeling Active Cell Movement With the Potts Model

Abstract: In the last decade, the cellular Potts model has been extensively used to model interacting cell systems at the tissue-level. However, in early applications of this model, cell movement was taken as a consequence of membrane fluctuations due to cell-cell interactions, or as a response to an external chemotactic gradient. Recent findings have shown that eukaryotic cells can exhibit persistent displacements across scales larger than cell size, even in the absence of external signals. Persistent cell motion has b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
30
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 29 publications
(31 citation statements)
references
References 58 publications
1
30
0
Order By: Relevance
“…We used periodic boundary conditions and a square lattice of size 1024 × 1024 sites. More details about initial conditions and thermalization can be found in [15].…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…We used periodic boundary conditions and a square lattice of size 1024 × 1024 sites. More details about initial conditions and thermalization can be found in [15].…”
Section: Resultsmentioning
confidence: 99%
“…However, when the friction term is present, we found that high density cultures exhibited a double-exponential for the velocity ACF, in contrast to an exponential characterizing the Brownian motion of low density cultures. For both densities the MSD behaves as a persistent random walk model for the time scale studied [15]. These results suggest that the complex behavior of cell motion can be consequence of the intrinsic feature of the movement, but also of cell-cell interactions.…”
Section: Introductionmentioning
confidence: 92%
See 3 more Smart Citations